Determinants of Generation Z Long Term Investment Interest Through Digital Literacy, Education and Risk Perception - Andi Mustika Amin; A. Reski Almaida Dg Maccening; Nidrah Nidrah; Fakhirah Husain (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose - This study examines the roles of digital financial literacy, digital financial education, and digital risk perception in shaping Generation Z’s long-term investment interest. The study addresses the gap between the rapid growth of digital investment platforms and the limited financial understanding that supports sustainable investment behavior. Design/methodology/approach – A quantitative approach with an associative research design was employed. Primary data were collected from 270 Generation Z respondents in Makassar using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Findings – The results indicate that digital financial literacy, digital financial education, and digital risk perception all have positive and significant effects on long-term investment interest. Financial literacy enhances individuals’ ability to evaluate financial information, financial education strengthens investment readiness, and rational risk perception increases confidence in making long-term investment decisions. Originality/value – This study demonstrates that Generation Z’s long-term investment interest is shaped by financial knowledge, educational experiences, and digital risk assessment. The findings highlight the importance of strengthening integrated digital financial literacy and education to encourage sustainable investment behavior among young investors.